1997
DOI: 10.1149/1.1838026
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Hydrogen on Ni/Yttria‐Stabilized Zirconia Cermet Anodes

Abstract: The oxidation of hydrogen on Ni/yttria-stabilized zirconia (Ni/YSZ) is studied by impedance spectroscopy. The active thickness obtained is 20 pm or less. Conditions such as temperature, anodic overvoltage, electrode potential, H2 and H20 partial pressure are varied. Three distinct arcs are identified in impedance spectra, representing at least three rate-limiting processes. One equivalent circuit of the type LR(RQ)(RQ)(RQ), where Q = Yjju4Th, is used to describe all recorded impedance in the temperature range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
225
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(254 citation statements)
references
References 7 publications
(10 reference statements)
23
225
2
1
Order By: Relevance
“…It can be found that the EAT increases from 8.1 μm to 9.4 μm under Vcell=0.8V as operating temperature T decreases from 1173K to 873K, which is consistent with results in [7]. On the contrary, [5,14,4,26] revealed that the EAT was negatively correlated with operating temperature T.…”
Section: Effect Of Operating Conditionssupporting
confidence: 86%
See 1 more Smart Citation
“…It can be found that the EAT increases from 8.1 μm to 9.4 μm under Vcell=0.8V as operating temperature T decreases from 1173K to 873K, which is consistent with results in [7]. On the contrary, [5,14,4,26] revealed that the EAT was negatively correlated with operating temperature T.…”
Section: Effect Of Operating Conditionssupporting
confidence: 86%
“…For the standard cell defined with parameters in Table. 3, the EAT is 8.1 μm (Vcell=0.8 V). Such a small value is in the range of [5,6,26,28,29], but differs a lot from [7,25,30]. The differences are probably caused by the quite different exchange current densities used in simulations.…”
Section: Resultsmentioning
confidence: 97%
“…This result indicates that the identified electrodeposition conditions used for depositing Ni onto Ag/GDC scaffold improved the performance of the anode, though the value remains greater than data reported in the literature for Ni/GDC and Ni/YSZ anodes fabricated using conventional and infiltration techniques (0.1-0.35 cm −2 ), [48][49][50][51] showing that more optimization is needed to further improve performance, and in this regard many process variables remain to be explored.…”
Section: Effect Of Additives-the Effect Of Non-anionic (Surfynol) Anmentioning
confidence: 68%
“…The strong dependence of the R H on temperature is typically associated with charge transfer process. 30 R L for HOR is essentially independent of applied dc bias and shows much less dependence on temperature (Figs. 7 and 9).…”
Section: O [4]mentioning
confidence: 99%